A computer aided biofeedback system - Aybey, İ. Melih. (Thesis (M.S.) - Bogazici University. Institute of Biomedical Engineering, 1986., 1986)
Biofeedback devices, unlike other medical devices, are not used in order to monitor a disordered physiological function. They are aimed to be used in training work to gain control over any physiological variable which may have no direct relation with the symptoms of the illness. This thesis reviews the theory and applications of biofeedback and presents an original design of a computerized biofeedback system (DBMl. The digital biofeedback monitor is a system which enables the therapist to analyze the data obtained during and after a biofeedback session by means of a digital computer. It can also be used by the patient for any kind of biofeedback treatment. Collected data related to the session can be stored onto a floppy disk for future references and analyses.
Keywords: Biofeedback training.; Biological control systems.; Feedback (Psychology)